Non-biological Complex Drugs (NBCDs): Complex Pharmaceuticals in Need of Individual Robust Clinical Assessment Before Any Therapeutic Equivalence Decision - Gaspar, Rogério Sá; Silva-Lima, Beatriz; Magro, Fernando; Alcobia, Armando; da Costa, Fernando Leal; Feio, José (Frontiers in Medicine, 2020)
Non-Biological Complex Drugs (NBCDs) are complex non-biological drugs comprising large high molecular weight molecules and, often, nanoparticular structures (including liposomes and block-copolymer micelles). In the case of NBCDs the entire complex is the active pharmaceutical ingredient and its properties cannot be fully characterized by physicochemical analysis. Moreover, the manufacturing process is fundamental to create the correct originator product. The same is true for generic versions of the product. A recent appraisal of approval procedures for NBCDs “follow-on products” approved in Europe shows a diversity of regulatory pathways. In fact three different abridged application procedures, under European legislation, were used: the generic application procedure of Article 10(1) the hybrid application procedure of Article 10(3), and the biosimilar application procedure of Article 10(4). Three informed consent applications via Article 10(c) from innovator companies of glatiramer acetate and sevelamer carbonate, were submitted shortly after the approval of the first follow-on products. Furthermore, a number of ‘well-established use’ applications (via Article 10(a)) were approved for iron sucrose and iron dextran complexes. In order to protect patients from the increased risks of NBCD products and NBCD follow-on products, two complementary approaches should be considered: (i) improving the regulatory procedures and their guidance documents within the pre-registration phase; (ii) not to consider interchangeability whenever clinical data is not available. With regard to the latter, the need for adequate safety and efficacy data might include also risk management programmes, within the post-approval pharmacovigilance actions. Certainly, that will depend on a risk appraisal that has to be considered for individual medicinal products, based on the nature of the submitted relevant set of safety/efficacy data.